Penggunaan Simbolisme Dalam Novel Laut Bercerita Karya Leila S Chudori: Kajian Semiotika - Dira Afrillya Tania; Memet Sudaryanto; Nia Ulfa Martha (Jurnal Kajian Ilmiah, 2026)
This study aimed to describe the use of symbolism in the novel Laut Bercerita by Leila S. Chudori through the lens of Roland Barthes’ semiotic theory. The novel contains a range of signs that depict traumatic experiences, state violence, and resistance against efforts to erase memory. The research employed content analysis with a qualitative descriptive approach. Data consisting of narrative excerpts, dialogues, and descriptive passages were examined using three levels of meaning: denotation, connotation, and myth. The findings showed that the five central symbols in the novel namely the sea, waves, four plates prepared every Sunday, the poem “On the Day of My Death,” and fish constructed layered meanings that functioned not only as aesthetic devices but also as ideological representations. These symbols illustrated how political violence penetrated domestic life, how the natural landscape was used to mask brutality, and how words persisted even when the body no longer existed. The study indicated that symbolism in the novel played an important role in shaping readers’ understanding of history, memory, and human suffering. It also demonstrated that literature can serve as a space to preserve memory and to foster conversations about past violence